2020
DOI: 10.33182/bc.v10i2.1161
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity and associated socio-economic factors among recent Syrian refugees in two Canadian cities

Abstract: In Canada, the prevalence of food insecurity is high among low-income households, particularly recent refugees. We evaluated the prevalence of food security among recent Syrian refugees and the associated factors in two Canadian cities, Toronto and Saskatoon. We collected data using the Household Food ‎Security Model, sociodemographic and socioeconomic questionnaires from 151 families. 84% of the Syrian households were food insecure, with no significant difference in prevalence between Saskatoon and Toronto. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 17 publications
2
15
2
1
Order By: Relevance
“…Results of this study revealed that 44.6% of Syrian refugees resettled in Ontario experienced food insecurity. These results contrast with a previously conducted study among resettled Syrian refugees in Toronto and Saskatoon, where a substantially higher prevalence of food insecurity (84%) was reported [13]. The difference in the rate of food insecurity could be attributed to variations in the definition of food insecurity utilized in our study compared to the previous one, where food insecurity was measured using categories of marginal, moderate, and severe, each with its distinct definition and subsequently merged [13].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Results of this study revealed that 44.6% of Syrian refugees resettled in Ontario experienced food insecurity. These results contrast with a previously conducted study among resettled Syrian refugees in Toronto and Saskatoon, where a substantially higher prevalence of food insecurity (84%) was reported [13]. The difference in the rate of food insecurity could be attributed to variations in the definition of food insecurity utilized in our study compared to the previous one, where food insecurity was measured using categories of marginal, moderate, and severe, each with its distinct definition and subsequently merged [13].…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, another study conducted in 2020 found that among Syrian refugees resettled in Toronto and Saskatoon, the overall prevalence of food insecurity was 84%, with 31% experiencing severe food insecurity, 41% experiencing moderate food insecurity, and the remaining experiencing marginal food insecurity. This study highlighted that households with an annual income below $40,000 were at a greater risk of food insecurity [13].…”
Section: Introductionmentioning
confidence: 86%
“…Afterwards, based on their situation, they could be eligible for regular social assistance programs. An abrupt cessation to federal government aid may explain the high prevalence of food insecurity among refugees in destination countries a year after arrival [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Refugees are provided aid for a short period of time, but many barriers such as language and lack of recognition of education from their home country makes it difficult to land jobs that pay well. For example, preliminary data indicates that 70% of Syrian refugees in Canada experience food insecurity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…En date du 31 janvier 2021, on comptait 44 620 réfugié.es syrien.nes réinstallé.es au Canada (Immigration Refugees Citizenship Canada, n.d.). À ce jour, de nombreuses études ont documenté et analysé les profils sociodémographiques (Al-Kharabsheh et al, 2020;Hanley et al, 2018;Kaida et al, 2020), les processus d'installation (Hamilton et al, 2020;Oudshoorn et al, 2020;Operational Data Portal, n.d.) et les différentes dynamiques d'intégration des réfugié.es syrien.nes réinstallé.es au Canada (Hanley et al, 2018;Haugen, 2019;Hynie et al, 2019;Walton-Roberts et al, 2020). Néanmoins, bien que la sélection pour une réinstallation au Canada soit faite dans un premier pays d'asile, souvent plusieurs années après que les personnes réfugiées y aient trouvé refuge (Hyndman et Giles, 2016), nous ne disposons que de très peu d'informations sur ces expériences prémigratoires et les parcours d'exil ayant précédé leur arrivée au Canada.…”
Section: Introductionunclassified